Blood composition of the reindeer. I. Haematology - Nieminen, Mauri; Timisjärvi, Jouni (Rangifer, 1981)
The semi-domestic reindeer is a ruminant which exhibits a highly advanced adaptation to the marked seasonality of the northern environment. Since the reindeer has an economic importance and previous information about its blood composition is scanty in respect to age, season, calving and nutrition, the haematology of 578 reindeer were studied. The blood samples were taken from the jugular vein mainly in connection with the marking of calves during summer and at reindeer round-ups in autumn and winter at 10 reindeer rearing subunits in Northern Finland in various seasons in 1973-79. The red blood cell count (8xl012/l), haemoglobin (108 g/1), packed cell volume (35%), white blood cell count (6x109/l) and serum iron (26 micromol/1) were low in newborn calves and reached their adult levels in autumn at the age of 5 months (average 11 x 1012/1, 182 g/1, 51%, 9x109/l, 44 micromol/1, respectively). The total serum bilirubin was relatively stable and vitamin B12 high in the first days after birth. The stable serum bilirubin indicates a relatively small breakdown of foetal erythrocytes. E-MCV of adult females was about 49 fl and the diameter of round erythrocytes about 5.5 microm and their thickness about 1.5 microm. No sickling was observed. The red cell osmotic fragility had a initial and final haemolysis points of 0.71 and 0.37% NaCl solution. The relative proportions of neutrophil, eosinophil and basophil granulocytes and agranular lymphocytes and monocytes were 52, 5, 2, 42 and 2 %, respectively. The calving of the reindeer occurs without visible haemorrhage. The body weight, red blood cell count, haemoglobin, packed cell volume and serum iron of pregnant hinds dropped, however, during the early lactation period, and a relative anaemia developed is partly due to iron deficiency and, perhaps, also breakdown of foetal erythrocytes. The means of body weight (range 50-70 kg), red blood cell count (8-11 x 1012/l), haemoglobin (118-185 g/1), packed cell volume (42-51%), white blood cell count (6-10 x 109/l), erythrocyte sedimentation rate (3-21 mm/hour) and serum iron (23-54 micromol/l) of free-grazing adult hind were highest in summer and autumn and decreased during winter. The lowest means were measured for the starved hinds in early spring. High body weight and blood haematological values were measured for the hinds fed on silage and molasses in winter.Poron veri. I. HematologiaAbstract in Finnish / Yhteenveto: Puolivilli poro on marehtija, joka on hyvin sopeutunut pohjoisen ympariston suuriin vuodenaikaismuutoksiin. Koska poro on tarkea hyotyelain, jonka veren koostumuksesta tiedetaan ian, vuodenajan, vasonnan ja ravitsemustilan suhteen varsin vahin, tutkittiin tyossa 578 poron hematologiaa. Verinaytteet otettiin poron kaulalaskimosta 10 eri paliskunnassa vasamerkinnan yhteydessa kesalla ja syys- ja talvierotuksissa vuosina 1973-79. Vastasyntyneen vasan veren punasolumaara (8xl012/l) hemoglobiinipitoisuus (108 g/1) punasolujen tilavuus osuus (35%), valkosolumaara (6x109/l) ja seerumin rautapitoisuus (26 micromol/1) olivat alhaiset ja saavuttivat aikuiset tasonsa syksylla 5kk:n iassa(keskimaarin 11 x 1012/1, 182 g/1, 51%, 9x109/l, 44 micromol/1). Seeruminkokonaisbilirubiinipitoisuus pysyi suhteellisen vakiona ja Bi2-vitamiini korkeana syntyman jalkeen. Bilirubiinipitoisuus osoittaa suhteellisen vahaisti sikiokauden punasolujen hajoamista. Aikuisen vaatimen punasolun keskitilavuus (E-MVC) oli 49 fl ja pyorean punasolun lapimitta 5.5 /xm ja paksuus 1.5 /j,m. Sirppisoluja ei havaittu. Punansolujen alkava hemolyysi vastasi 0.71% NaCl-liuosta ja taydellinen hemolyysi 0.37% NaCl-liuosta. Neutrofiilisten, eosiniofiilisten seka lymfosyyttien ja monosyyttien suhteelliset osuudet olivat 52, 5, 2, 42 ja 2%. Vaikka vasonta tapahtuu ilman nakyvaa verenvuotoa, kantavien vaadinten ruumiinpaino, punasolumaara, hemoglobiinipitoisuus, punasolujen tilavuusosuus ja seerumin rautapitoisuus laskivat imetyksen alkuvaiheessa ja syntynyt anemia johtui mahdollisesti raudan puutoksesta tai raskauden ajan punasolujen haviamisesta. Vapaana laiduntavan vaatimen ruumiinpaino (vaihtelu 50-70 kg), punasolumaara (8-11 x 1012/l), hemoglobiinipitoisuus (118-185 g/1), punasolujen tilavuusosuus (42-51%), valkosolumaara (6-10 x 109/l), lasko (3-21 mm/t) ja seerumin rautapitoisuus (23-54 micromol/l) olivat korkeimmillaan kesalla ja syksylla ja laskivat talvella. Alhaisimmat pitoisuudet mitattiin nalkiintyneille vaatimille varhaiskevaalla. Korkeat veriarvot ja ruumiinpainot mitattiin vaatimille, joita oli ruokittu talvella sailorehulla ja melassilla.Renblod. I. HematologiAbstract in Swedish / Sammandrag: Renen, ett halvtamt boskapsdjur, år en idisslare med hog anpassningsformåga till de stora omvåxlingarna av de olika årstiderna som år karakteristiska for de nordliga regionerna. Eftersom renen år ekonomiskt betydelsesfull och man tidigare i ganska liten utstråckning undersokt dess blodsammansåttning, undersoktes 578 renar hematologiskt. Blodproven togs från vena jugularis i samband med oronmårkning av kalvarna på sommaren och i samband med skiljning av 10 renbeteslag på hosten och vintern i norra Finland under olika såsonger 1973-79. Hos nyfodda kalvar var foljande vården låga: mångden av roda blodkroppar (8xl012/l), hemoglobin (108 g/l), hematokrit (35%), vita blodkroppar (6x109/l), serumjårnhalt (26 micromol/1). Dessa vården nådde nivån av ett vuxet djur på hosten i en alder av 5 månader (respektive medeltal 11 x 1012/1, 182 g/1, 51%, 9x109/l, 44 micromol/1). Totalvårdet for serum bilirubin visade sig vara relativt stabilt och B12 vitaminhalten var hog under de forstå dagarna efter fodseln. Det stabila serum bilirubinvårdet tyder på en relativt liten splittring av fetala erytrocyter. E-MCV hos vuxna renkor var ca. 49 fl, de runda erytrocyternas diameter ca. 5,5 microm och deras tjocklek ca. 1,5 microm. Några «sickligs» (skårvaktiga celler) kunde inte konstateras. De roda blodkropparnas osmotiska splittring startade i en NaCl-losning av 0,71% och var total vid 0,37%. De relativa proportionerna av neutrofil-, eosinofil- och basofilgranulocyter samt av agranulåra lymfocyter var respektive 52, 5, 2, 42 och 2%. Renarnas kalvning sker utan synbar blodning. Hos gravida renkor sjånk mångden av roda blodkroppar såsom hemomglobin och hematokrit. Den under den forstå tiden av kalvarnas amning forekommande relativa anemin beror emellertid på jårnbrist och eventuellt också på splittring av de fetala erotrocyterna. Hos fritt betande vuxna renkor var foljande vården som hogst under sommaren och hosten och sjonk under vintern: medelkroppsvikt (50-70 kg), mångden av roda blodkroppar (8-11 x 1012/l), hemoglobin (118-185 g/l), hematrokrit (42-51%), vita blodkroppar (6-10 x 109/l), erytrocytsånkan och serumjårnhalt (23-54 micromol/l). De lågsta medelvården mattes tidigt på våren hos fastande renkor. Kroppsvikten och blodets hematologiska vården var hoga hos sådana renkor, vilka om vintern matats med ensilage eller melasse.